Solving Ordinary Differential Equations with Variable Coefficients Using the New Bayawa Transform (Al-Qalaa Journal, 2024)
A new integral transform was applied in this paper to find the solution of ordinary differential equations (ODEs) with variable coefficients. ODEs are of great importance in various scientific fields, especially physical and applied mathematics.The new integral transform is called Bayawa transform. Bayawa transform is one of the modern transformations that have been developed in recent months. The Bayawa transform can be solved ODEs with constant coefficients in general. Furthermore, it can be used to solve ODEs with variable coefficients, which was discussed by this paper.